Edukasi dan Inovasi Lingkungan dalam Program KKN: Vertical Garden sebagai Model Mitigasi Mikro UHI di Gorontalo - Rahmayanti; Lydia Tatura; Niniek Pratiwi; Syafriani (Journal of Applied Social Science, 2025)
The development of vertical gardens in dense settlements offers an innovative model for micro-level Urban Heat Island (UHI) mitigation. This study documents the implementation of the Community Service Program (KKN) at Daenaa Village, Gorontalo, emphasizing education, social participation, and environmental innovation. Using a qualitative descriptive method, data were obtained from field observations, interviews, and participatory documentation. The findings highlight that vertical garden installations not only enhance local microclimate comfort but also function as learning media for environmental awareness. The community’s enthusiasm and involvement indicate the success of participatory learning in fostering sustainable green practices. This initiative demonstrates that small-scale ecological interventions can yield meaningful social and environmental impacts in rural-urban transition areas.